In Utero Vertical Transmission of Coronavirus Disease 2019 in a Severely Ill 29-week Preterm Infant - Gupta, Arpit; Malhotra, Yogangi; Patil, Uday; Muradas, Ana R.; Lee, William T.; Krammer, Florian; Amanat, Fatima; Clare, Camille A.; Vinod, Suja; Ghaly, Emad (American Journal of Perinatology Reports, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) or coronavirus disease 2019 (COVID-19) is currently in worldwide pandemic state with very limited data about the mode of transmission to the growing fetus. There are a few published cases of COVID-19 infection in the infants born to COVID-19 positive mothers where most of the reported cases were either mildly symptomatic with positive COVID-19 polymerase chain reaction (PCR) or had negative COVID-19 PCR raising the question of vertical transmission. We present a case of likely intrauterine transmission of COVID-19 infection in a critically ill premature infant born to a COVID-19 infected mother and describing her clinical course thus far. The clinical presentation in the infant is consistent with COVID-19 infection described so far in literature along with positive PCR, and positive COVID-19 serology: immunoglobulin G, immunoglobulin M, and immunoglobulin A.
Keywords: Severe acute respiratory syndrome coronavirus 2; coronavirus disease 2019; preterm; newborn; vertical transmission; intrauterine